Perlindungan Hukum Konsumen Fintech P2P Lending akibat Penagihan oleh Pihak Ketiga sesuai POJK No.22 Perlindungan Konsumen - Richard Ratuwalu; Komsatun Komsatun; Sanny Dewayani (Pusat Riset dan Inovasi Nasional, 2026)
The rapid growth of financial technology (fintech) Peer-to-Peer Lending (P2PL) in Indonesia has created both opportunities and challenges, particularly regarding debt collection practices by third parties (debt collectors). Such practices often result in violations of consumer rights, including intimidation, harassment, and breaches of privacy. To address these issues, the Financial Services Authority of Indonesia (OJK) issued Regulation No. 22 of 2023 on Consumer and Public Protection in the Financial Services Sector, which establishes legal standards for protecting fintech P2PL consumers. This study aims to analyze the regulation of debt collection by third parties under OJK Regulation No. 22/2023, assess the forms of legal protection for consumers, and identify the obligations of fintech P2PL providers in managing collection practices. The research applies a normative juridical method with statutory and conceptual approaches. The findings indicate that OJK Regulation No. 22/2023 provides consumer protection through preventive mechanisms (mandatory transparency, prohibition of intimidation, and regulation of third-party involvement) and repressive mechanisms (complaint handling and administrative sanctions). However, challenges remain in implementation, such as low consumer literacy, outsourced collection practices, and weak on-site supervision. Therefore, stronger regulation, tighter controls by providers, and collaboration among regulators, law enforcement, and fintech associations are required to ensure optimal consumer protection.